Pengaruh Pendidikan Multikultural terhadap Sikap Toleransi Mahasiswa dengan Pemahaman Pluralisme sebagai Variabel Mediasi - Nur Asyiah Siregar; Hotni Sari Harahap (Fakultas Agama Islam Universitas Al Washliyah, 2026)
Students' tolerance remains a challenge in higher education institutions despite the diverse religious, ethnic, cultural, and social backgrounds of the academic community. This study aims to examine the effect of multicultural education on students' tolerance attitudes, the effect of multicultural education on pluralism understanding, the effect of pluralism understanding on tolerance attitudes, and the mediating role of pluralism understanding in the relationship between multicultural education and tolerance attitudes. A quantitative approach with an explanatory survey design was employed. The sample consisted of 76 students from Universitas Alwashliyah selected through proportionate stratified random sampling. Data were collected using questionnaires and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings reveal that multicultural education has a positive and significant effect on pluralism understanding (?=0.911; t=39.749) and tolerance attitudes (?=0.539; t=2.795). Pluralism understanding also has a positive and significant effect on tolerance attitudes (?=0.392; t=2.161) and partially mediates the relationship between multicultural education and tolerance attitudes (?=0.357; t=2.096). It can be concluded that strengthening multicultural education accompanied by enhanced pluralism understanding plays an important role in fostering students' tolerance in higher education.